Reforming of land management system under authority of decentralization - Dorosh, O.; Melnik, D.; Sviridova, L. (Land Management, Cadastre and Land Monitoring, 2017)
The article is devoted to the problems related to the reform of land management from the beginning of the land reform ill the presentine. This need has arisen due to making another attempt to reorganize the structure of the land structures. With the launch of the land reform established the State Committee of Ukraine for Land Resources in 1992. To speed up land reform and land privatization in 2001 formed the administrative bodies of the State Committee for Land Resources of Ukraine. In order to improve the system of state land management in 2011 created the State Agency of Land Resources of Ukraine, which was reorganized in 2014 into the State Service of Ukraine of geodesy, cartography and cadastre. Over the years, in order to "optimize" the system of central executive body, content of this body has not been changed and constantly was changing its name and subordination, namely: the State Committee for Land Resources - Ministry of Ecology and Natural Resources of Ukraine, the State Agency of Land Resources of Ukraine - Ministry of Agrarian policy and Food of Ukraine, State Service of Ukraine of geodesy, cartography and cadastre - Ministry of regional development, construction and housing. On the basis of analysis concerning the powers of the central executive authorities, local authorities found that the newly farmed Service State Land Cadastre das not contribute to the effectiveness of the administration, especially at the national level, as these features ave not provided by "Regulations on State Land Cadastre " and other regulations. In addition, the local level detected removal of local government in matters of land relations. In conclusion, proposed system based redistribution of powers on the level of central executive bodies and local authorities to reform the system of land management with regard to decentralized processes in Ukraine. It is advisable to restore central authority for land reform and regulation of land relations to the structure of the executive authorities in coordinating its activities directly to the Cabinet of Ministers of Ukraine or the Ministry of Agrarian Policy and Food of Ukraine and provide the following powers: ü development of legislation in the sphere of land relations for the development and implementation of the state land policy; ü coordination of the completion of land reform; ü cadastre at national level; ü land management at the national level; ü monitoring at the national level; ü state control over the land use and land protection. State Service of Geodesy and Cartography post in the Ministry of Regional Development, Construction and Housing and Communal Services of Ukraine Local governments provide the following powers: • implementation of land policy at regional and local levels; • Organization of Land Management; cadastre, land protection. •transfer the right to control agricultural lands within the territories of Commons as faras the institution of land zoning is established. Keywords: management of land resources, Goskomzem, Goszemagenstvo, Derzhgeokadastr, Ministry of Regional Development, Ministry of Agricultural Policy, functions, powers, central executive authorities, local self-government.